The effects of carvedilol on ischemia-reperfusion injury in the rat testis - Parlaktas,B.S. (2014)
Objective: To analyze the oxidative damage and histopathological alterations caused by ischemia-reperfusion (I/R) injury and ameliorative effects of carvedilol (CVD) in the rat testis. Materials and Methods: Twenty-one male rats were randomized into 3 groups as follows: Group I (n = 7); control (sham) group, Group II (n = 7); I/R group, in which I/R injury was performed by torsing the left testis 720º clockwise for 2 hours and detorsing for 2 hours. Group III (n = 7); CVD treatment group; in addition to I/R process, one-dose of CVD was administered (2mg/kg, i.p) 30 min. before detorsion. Levels of antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and levels of malondialdehyde (MDA) and protein carbonyl (PC) were determined in testicular tissues and serum of rats. Testicular tissues were also examined histopathologically and Johnsen scores were determined. Results: Activities of SOD and GSH-Px in serum and testicular tissues were increased by I/R, but administration of CVD decreased these levels (p < 0.001 and p = 0.001). Significantly increased MDA levels in serum and testicular tissues were decreased by CVD treatment (p < 0.001 and p = 0.001). Concerning PC levels in serum and testicular tissues, there was no statistically significant difference between the groups (p = 0.989 and p = 0.428). There was not a statistically significant difference in terms of mean Johnsen scores between the groups (p = 0.161). Conclusions: Administration of CVD decreased oxidative damage biochemically in the rat testis caused by I/R injury, but histopathologically no change was observed between all of the groups.